Genome-wide identification of the class III peroxidase gene family and its association with fruit rind cracking in Cucumis melo - Hu, Yanping; Zhang, Tingting; Wang, Yushan; Wang, Chongchong; Zhu, Baibi; Wang, Feng; Chen, Yisong; Wang, Min; Zhou, Yang (Frontiers in Plant Science, 2026)
IntroductionClass III peroxidase (PRX) functions as a pivotal enzyme in lignin polymerization and participates in the regulation of cell wall hardening and elongation. Nevertheless, comprehensive investigations on PRX involvement in the rind cracking of melon (Cucumis melo) remain absent.MethodsIn this study, melon was used as experimental material. Physiological analyses were performed to compare peroxidase activity and lignin accumulation between cracking-susceptible and resistant cultivars, as well as between cracked and non-cracked rinds. Genome-wide identification, phylogenetic analysis, chromosome localization, collinearity analysis, and cis-acting element prediction were conducted to characterize the melon PRX gene family. Transcriptome sequencing was used to analyze CmPRX expression patterns across different rind types, and quantitative real-time polymerase chain reaction (qRT-PCR) was performed for validation. Protein-protein interaction networks were predicted to explore the functional associations of candidate genes.Results and discussionPeroxidase activity and lignin accumulation were significantly higher in cracking-susceptible cultivars compared to cracking-resistant cultivars, with cracked rinds displaying elevated levels relative to intact rinds. Sixty-four PRX genes were identified in the melon genome, and phylogenetic analysis categorized them into six subgroups. The CmPRX genes were unevenly distributed across 12 chromosomes, and collinearity analysis uncovered eight duplicated gene pairs within the melon genome. Comparative synteny analysis revealed that the number of collinear PRX gene pairs between melon and other Cucurbitaceae species, specially cucumber and watermelon, was greater than that observed with the more distantly related Arabidopsis. Promoter cis-acting element examination revealed that the 64 CmPRX genes harbored 25 classes of elements associated with hormones, stress responses, and growth and development. Transcriptome data from melon rinds revealed that the CmPRX genes could be clustered into six groups based on expression patterns across different rind types. Among these, CmPRX genes in clusters 1 and 6 exhibited higher transcript levels in cracked rinds compared to non-cracked rinds. Moreover, quantitative real-time polymerase chain reaction analyses confirmed that CmPRX39, CmPRX48, and CmPRX51 were expressed at significantly elevated levels in cracked rinds compared with those of non-cracked rinds. Protein interaction network prediction showed that these three candidate genes interacted with multiple proteins involved in the lignin synthesis pathway, suggesting their potential regulatory roles in rind cracking of melon through mediating lignin polymerization. These findings identified candidate genes influencing rind cracking in melon, thereby offering potential molecular targets for the breeding of cracking-resistant cultivars.